Political reforms in the gulf states: Responses from Indonesia - Aswar, Hasbi (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2025)
Over the years, there has been a revolution in political reforms in the Gulf Countries. These reforms involve the promotion of tolerance, increased expression, and the position of women, breaking down traditional Islamic values, and assuming more liberal Western ideologies. The reforms also include the empowerment of women, trimming the powers vested in the religious police, and promoting moderate Islam. This study seeks to elaborate on the responses of the Indonesian government and Muslim figures toward political reforms. This study uses a qualitative method by collecting secondary data from online sources and analyzing the Indonesian government and figures responses to the Gulf countries religious reforms. The study found an enthusiastic response from the government level to the reforms through regular visits and event collaboration between Indonesia and the Gulf especially with Saudi Arabia. On the one hand, Muslim figures responded to it not so enthusiastically and only limited comments by several figures from different Islamic groups in Indonesia.